Outcomes of Root Canal Treatment: 2 Years Experience in Community Based Medical College, Bangladesh Hospital - Hossen, Mahbuba; Siddique, Mazharul Alam; Ansary, Nahid Binte (Community Based Medical Journal, 2013)
This retrospective study was done in the Department of Dentistry, CBMCB hospital from January2009 to December2010. 223 patients who underwent RCT were purposively selected. Male-female ratio was 1:1.4, mean age of patients were 28.4 years. Most common indication of RCT was gross caries 69.95%, common complications were fractured crown 11(57.89%), tenderness 5(26.32%), discharging sinus 2(10.53%). Over all success rate of RCT was 91.48%. DOI: http://dx.doi.org/10.3329/cbmj.v2i1.14178 Community Based Medical Journal Vol.2(1) 2013 29-33